Creating opportunities for improving lake‐focused stakeholder engagement: knowledge–action systems, pro‐environment behaviour and sustainable lake management. Issue 1 (26th March 2013) - Bell, Kathleen P.; Lindenfeld, Laura; Speers, Ann E.; Teisl, Mario F.; Leahy, Jessica E.
Abstract: Managers, policymakers, non‐government organizations and community groups are increasingly relying on stakeholder participation to bolster lake management efforts. The growing portfolio of lake‐focused stakeholder engagement cases offers valuable information about the efficacy of alternative stakeholder engagement strategies. While attention has been devoted to inventorying these instances, lesser emphasis has been given to evaluating the effectiveness of different participation and engagement approaches. There is arguably no panacea for involving stakeholders in lake and basin management. Lake management challenges in distinct natural and human systems necessitate diverse approaches for interacting with stakeholders. As calls for stakeholder participation increase and management budget constraints tighten, the urgency of exploring and documenting the effectiveness of alternative approach rises. This paper examines lake‐focused stakeholder participation activities targeting individuals and households, summarizes and shares recent findings from research of knowledge–action processes and pro‐environment behaviours, and offers encouragement and guidance for lake managers to create opportunities for improving lake‐focused stakeholder engagement.